Activated Protein C Attenuates Experimental Autoimmune Encephalomyelitis Progression by Enhancing Vascular Integrity and Suppressing Microglial Activation - Kant, Ravi; Halder, Sebok K.; Fernández, Jose A.; Griffin, John H.; Milner, Richard (Frontiers in Neuroscience, 2020)
Background: Activated protein C (APC), a serine protease with antithrombotic effects, protects in animal models of ischemic stroke by suppressing inflammation and enhancing vascular integrity, angiogenesis, neurogenesis and neuroprotection. A small number of animal studies suggest it might also have therapeutic potential in multiple sclerosis (MS), though results have been mixed. Based on these conflicting data, the goals of this study were to clarify the therapeutic potential of APC in the experimental autoimmune encephalomyelitis (EAE) model of MS and to determine mechanistically how APC mediates this protective effect. Methods: The protective potential of APC was examined in a chronic progressive model of EAE. Vascular breakdown, tight junction protein expression and vascular expression of fibronectin andintegrin as well as vascularity and glial activation were analyzed using immunofluorescence (IF) of spinal cord sections taken from mice with established EAE. The direct influence of APC on microglial activation was evaluated in vitro by a combination of morphology and MMP-9 expression Results: APC attenuated the severity of chronic progressive EAE, and this was strongly associated at the histopathological level with reduced levels of leukocyte infiltration and concomitant demyelination. Further analysis revealed that APC reduced vascular breakdown which was associated with maintained endothelial expression of the tight junction protein zonula occludens-1 (ZO-1). In addition, APC suppressed microglial activation in this EAE model and in vitro studies revealed that APC strongly inhibited microglial activation at both the morphological level and by the expression of the pro-inflammatory protease MMP-9. Conclusions: These findings build on the work of others in demonstrating strong therapeutic potential for APC in the treatment of inflammatory demyelinating disease and suggest that enhancement of vascular integrity and suppression of microglial activation may be important mediators of this protection.